Knowledge, Attitude & Behaviors Related to Oral Health among Students & Faculty of Ayub Medical College, Abbottabad, Pakistan - Nabbiya Noor; Asifa Zubair; Sadia Saeed; Omaima Arshad; Noreen Sultan; Wasim Ejaz (Gandhara University, 2022)
OBJECTIVES: The aim of this study was to analyze the knowledge, attitude and practices of medical students and faculty related to oral health. METHODOLOGY: A cross-sectional study was conducted at Ayub Medical College, Abbottabad Pakistan comprising of medical students and their teaching faculty. The participants out of total 400 distributed data forms responded 330 questionnaires positively. Data analysis was performed using SPSS software version 25.0 (using descriptive analysis and Chi Square test). P value of less than 0.05 was statistically significant. RESULTS: The survey revealed that the high proportion (96.6%) of teachers knew about dental caries, which was significantly higher than students (p-value 0.031).  High percentage of teachers had habit of brushing twice daily as compared to students (p=0.001). CONCLUSION: Within limitations of this survey, teaching faculty possessed better knowledge, attitude and behavior related to oral health as compared to medical students.